2010
DOI: 10.1080/01635581003605979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Intake of Isoflavones on the Estrogen and Progesterone Receptor Status of Breast Cancer

Abstract: To examine if higher intake of isoflavones prior to diagnosis was associated with a positive status of estrogen receptors (ER) and progesterone receptors (PR) in breast tumor tissue, a retrospective study was conducted in 2004 to 2005 in 756 Chinese women with histologically confirmed breast cancer. We administered a food frequency questionnaire by face-to-face interview to assess the intake of the isoflavones daidzein and genistein. Unconditional logistic regression analysis was used to estimate odds ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In other studies phytoestrogens have been shown to relate to breast cancer characteristics at diagnosis, for example an increase in dietary lignans [27] and isoflavones [28] have been found to be associated with ER positive tumours. Higher lignan consumption has been related to a reduction in lymphovascular invasion, and smaller tumour size [29], although the Australian population studied had an order of magnitude higher lignan intake levels compared with the DietCompLyf cohort (between 1,640 and 2,260 µg/d from an FFQ).…”
Section: Expected Outcomes Of Dietcomplyfmentioning
confidence: 94%
“…In other studies phytoestrogens have been shown to relate to breast cancer characteristics at diagnosis, for example an increase in dietary lignans [27] and isoflavones [28] have been found to be associated with ER positive tumours. Higher lignan consumption has been related to a reduction in lymphovascular invasion, and smaller tumour size [29], although the Australian population studied had an order of magnitude higher lignan intake levels compared with the DietCompLyf cohort (between 1,640 and 2,260 µg/d from an FFQ).…”
Section: Expected Outcomes Of Dietcomplyfmentioning
confidence: 94%
“…Of the 44 studies, 30 reported risk ratios and confident intervals relating to the risk of breast cancer; these are displayed in Figures 2 - 3 [42-49,51,52,56,57,61-65,68,70-73,75,76,78,80,81,83,84]. Fourteen studies did not report associations as odds ratios with confidence for overall risk of breast cancer, and so were not included in the figures [41,53-55,58-60,66,67,69,74,79,82,83]. …”
Section: Resultsmentioning
confidence: 99%
“…Overall, of the 44 case control studies, 32 showed that higher consumption of soy foods and/ or soy isoflavones was associated with lower risk for primary breast cancer [42-46,49-51,53,54,56-58,61-64,66,71-73,75,77-79,81,83], breast cancer mortality [55], or improved markers of prognosis (ER+ status vs receptor negative status) [74,82] among the overall study population. None of the case control studies examined effects on recurrence or association with use of tamoxifen.…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies have showed a lowering effect of PEs over breast carcinogenesis. Significantly reduced tumor growth after consumption of genistein and soy extracts in the mouse (Kim et al, 2008), better prognosis in breast cancer patients with higher plasma genistein levels (Iwasaki et al, 2008), higher frequency of ER and PR positivity, resulting probably in better cancer prognosis (Zhang et al, 2010), overall decrease in premenopausal breast cancer (Morimoto et al, 2012) -merely in overweight women (Cotterchio et al, 2008)-or postmenopausal disease (Goodman et al, 2009;Buck et al, 2010;Anderson et al, 2012;Zaineddin et al, 2012) -especially ER+PR+ tumors (Anderson et al, 2012) with more frequent use of PE, have all been detected in different valuable studies.…”
Section: Discussionmentioning
confidence: 99%